L2 motivation, anxiety and self-efficacy: The interrelationship of individual variables in the secondary school context - Piniel, Katalin; Csizér, Kata (Studies in Second Language Learning and Teaching, 2013)
Our study describes the relationship of second language learning motivation, self-efficacy, and anxiety; that is, how motivation, cognition, and affect might interact during the process of second language learning. Questionnaire data were collected from 236 Hungarian students studying at various secondary schools. Structural equation modeling was used to investigate the proposed circular relationship of students’ motivated learning behavior, language learning experience, self-efficacy beliefs, and both debilitating and facilitating anxiety. Our results indicate that: (a) the process of motivation is complex and influenced by other individual difference (ID) variables, and (b) the investigation of ID variables in constellations rather than in isolation seems to be more fruitful in understanding language learner differences.